Wastewater Treatment Plant (WWTP) Bahagia Market on Kuala Dua Village Subdistrict Sungai Raya - Shintiya Murhaliza Fitri; Isna Apriani; Yulisa Fitrianingsih (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2023)
Location of Bahagia Market on K.H. Abdurrahman Wahid streets, Kubu Raya regency. Bahagia Market has been operation for two years but doesn’t have wastewater treatment, the liquid waste product is discharged directly into the waters. The purpose of this plan is to knowing the discharge of wastewater generated, so the treatment is adjusted to the quality of wastewater and the available land area, as well as calculating cost budget. Planning methods is area survey, data collection, waste inventory, sampling, quality analysis, calculation of wastewater discharge, planning of wastewater treatment, and calculation of cost budget. The planning results are Bahagia market has 11 stalls, 64 loss and 43 tables with 3 drains. The liquid of wastewater come from the washing of vegetables, fish, meats, and poultry. BOD, COD, TSS, and ammonia parameters are above quality standards, while total coliform, fat and oil are below quality standards. Wastewater treatment project for the 5 next years starting from 2023 to 2027 with wastewater effluent is 8640 liters/days. Treatment unit use are sump well, bar screen, rotating biological contactor, settling basins, disinfection tub, and sludge drying bed with a land area of 5 m2 and a cost budget of Rp. 69,315,479.